Struvite as a sustainable fertilizer: nutrient recovery from corn starch wastewater with minimal sludge production - Li, Hongyan; He, Yong; Long, Beisheng; Li, Xiaodan; Tian, Xi; Li, Songsong; Ma, Li (Frontiers in Water, 2025)
IntroductionThe deep-processing corn industry produces nutrient-rich wastewater that exacerbates eutrophication in water bodies, necessitating the development of sustainable nutrient-recovery methods.MethodsThis study introduces a sensor-integrated struvite crystallization method for nitrogen (N) and phosphorus (P) recovery from cornstarch wastewater through struvite crystallization.ResultsUsing real-time pH and ion sensors, the conditions were optimized (pH 10.50, Mg/P ratio 2.0, 30°C, 35 min, 180 rpm), which recovered 98.52% of P and high N rates. Single-factor and orthogonal experiments identified pH and Mg: P ratio as the primary factors that influenced recovery, with aquatic temperature, reaction time, and stirring rate as secondary factors. X-ray diffraction, scanning electron microscopy, and energy-dispersive X-ray spectroscopy were used to confirm the rod-shaped struvite morphology and purity magnitude. Compared to biochar (89% N recovery) and algal systems, our approach reduced chemical inputs by 30% and sludge inputs by 40%, supporting circular economic principles. Pot experiments validated the efficacy of struvite as a slow-release fertilizer and its ability to enhance vegetable growth.DiscussionThis sensor-driven method offers an innovative and eco-friendly solution for managing agro-industrial wastewater.ConclusionThis mitigates eutrophication and promotes resource recovery in the corn-processing industry.